Alison and Bob play a game with coins. Alison starts with 2 coins while Bob starts with 1. Each turn, if Alison has a coins and Bob has b coins, Alison has a 3 b chance of receiving 1 coin from Bob and a 3 a chance of giving Bob 1 coin. Let A ( n ) denote the expected number of coins Alison has after n turns. The value of ∑ i = 1 ∞ ( A ( i ) − lim n → ∞ A ( n ) ) is equal to q p with co-prime positive integers p , q . Find p + q .
Check out Part II here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If Alison has a coins and Bob has 3-a coins after (n-1) turns then:
A(n) = 3 a × (a-1) + 3 3 − a × (a+1)= probability of losing a coin times no. of coins after change + probability of gaining a coin times no. of coins after change
a = A(n-1) by definition
After a bit of rearrangement: A(n) = 1 + 3 A ( n − 1 )
as n gets larger, A(n) tends to 1.5 as it is the only stable equilibrium since:
if A(n)=1.5 then A(n+1) = 1.5
if A(n)>1.5 then A(n+1)<A(n)
if A(n)<1.5 then A(n+1)>A(n)
let S = ∑ i = 1 ∞ A(i) - 1.5
then 3 S = ∑ i = 1 ∞ 3 A ( i ) - 0.5 = ∑ i = 2 ∞ A(i) - 1.5 using the recurrence relationship
S = 3 S + 6 1
S = 4 1
Problem Loading...
Note Loading...
Set Loading...
We can see that A ( 0 ) = 2 and A ( 1 ) = 3 1 × 3 + 3 2 × 1 = 3 5 , and can define A ( n ) recursively.
If Alison has r coins after x turns where x ≤ n − 2 and r = 1 or 2 , she has a 3 2 chance of having 3 − p coins and 3 1 chance of having 0 (if p = 1 ) or 3 (if p = 2 ) coins after one turn. In the latter case, she will have a 3 1 chance of having p coins again after the ( x + 2 ) t h turn. This means that A ( x ) = 3 2 ( 3 − A ( x − 1 ) ) + 3 1 A ( x − 2 ) . Note that ( x − 1 ) and ( x − 2 ) were used instead of ( x + 1 ) and ( x + 2 ) because the ( x + 1 ) t h turn is one turn closer to turn n than the x t h turn. The above expression simplifies to A ( x ) = 2 − 3 2 A ( x − 1 ) + 3 1 A ( x − 2 ) .
If Alison has s coins after x turns, where s = 0 or 3 , she will certainty have 1 or 2 coins respectively after one turn. Therefore, after the ( x + 2 ) t h turn, she will have a 3 1 chance of having s coins again and 3 2 chance of having 2 or 1 coins respectively—this means that there is a probability of 3 2 that the number of coins she has after the ( x + 1 ) t h turn and that after the ( x + 2 ) t h turn sum up to 3 . In this case, we also arrive at the conclusion that A ( x ) = 3 2 ( 3 − A ( x − 1 ) ) + 3 1 A ( x − 2 ) , meaning that A ( x ) = 2 − 3 2 A ( x − 1 ) + 3 1 A ( x − 2 ) no matter how many coins Alison has after x turns.
Solving the recurrence relation with the initial conditions stated above, we get A ( n ) = 2 3 + 2 × 3 n 1 . Therefore, lim n → ∞ A ( n ) = 2 3 and ∑ i = 1 ∞ ( A ( i ) − lim n → ∞ A ( n ) ) = ∑ i = 1 ∞ 2 × 3 i 1 = 2 1 × 2 1 = 4 1 , giving the answer of 5 .